Foreign Aid to Timor-Leste and the Rise of China (Journal of International Studies, 2020)
Foreign aid forms an important part of a stateâ€™s identity within the international system. The established dichotomy saw developed countries giving aid, while developing countries were receiving it. Nevertheless, Chinaâ€™s â€˜riseâ€™, along with that of other â€˜emerging economiesâ€™, changed such a dualist view; or at least undermined the traditional concept of aid giving. China is becoming a world power, it is the second largest economy, yet it is still within the group of developing countries. However, it provides a considerable amount of foreign aid worldwide. This is destabilizing the established understandings of aid regimes, as set by the Development Assistance Committee (DAC) donors since the 1950s. In particular, the rise of China in Timor-Leste as an important aid contributor, but working outside the leading aid regime, is affecting the most prominent donor in the country, Australia. Moreover, the rapidly growing presence of China in Timor-Leste seems well received by the local government, although criticism arose amongst the population. Thus, this paper attempts to analyse the issue from different levels. Firstly, it will analyse how China managed to â€œbreakâ€ the monopoly of Australian aid by accessing Timor-Leste. It will then explicate the principles and the practices of Chinese aid, and will attempt to establish whether Chinese aid has produced a positive economic impact on Timor-Leste and its people. Finally, this paper suggests that Chinese aid is not challenging, neither threatening the Australian aid assistance in Timor-Leste; rather Chinese aid offers an alternative way of giving aid, and which can also convey to Australia with the possibilities of establishing mutual benefits and effective partnerships with the recipient countries.